2011
DOI: 10.1038/nn.2958
|View full text |Cite
|
Sign up to set email alerts
|

Orientation tuning of cytochrome oxidase patches in macaque primary visual cortex

Abstract: The abundant concentration of cytochrome oxidase in patches or blobs of primate striate cortex has never been explained. Patches are thought to contain unoriented, color-opponent neurons. Lacking orientation selectivity, these cells might endow patches with a high level of metabolic activity because they respond to all contours in visual scenes. To test this idea, orientation tuning was measured in layer 2/3 of macaque V1 using acutely implanted 100-electrode arrays. Each electrode recording site was identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 50 publications
3
22
1
1
Order By: Relevance
“…3 A and C), respectively. We further examined statistically how well these two clusters separated from each other by the methods of two-group k-means clustering and the silhouette values (39,40). The computed silhouette values showed that for each monkey, only two of the 39 data points had negative silhouette values (gray dots in Fig.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…3 A and C), respectively. We further examined statistically how well these two clusters separated from each other by the methods of two-group k-means clustering and the silhouette values (39,40). The computed silhouette values showed that for each monkey, only two of the 39 data points had negative silhouette values (gray dots in Fig.…”
Section: Significancementioning
confidence: 99%
“…The distribution of the comparison of single neuron's CC values between two alignments was tested by using the k-means clustering analysis (MATLAB version 7.9.0; MathWorks) (40). To evaluate objectively how well the clustering analysis fits with the experimental data, the silhouette value of each data point, which measures the confidence level of a data point belonging to a cluster, was computed.…”
Section: Neural Data Analysismentioning
confidence: 99%
“…All primates seem to have a pattern of cytochrome oxidase (CO)-rich blobs (reflecting high metabolic activity) within interblob surrounds of lower CO levels (23)(24)(25). Neurons in the blobs respond to color, are less selective for stimulus orientation, and have higher firing rates than neurons between the blobs (7,(26)(27)(28)(29). However, blobs and interblob regions are found not only in primates with trichromatic or dichromatic color systems but also in nocturnal primates with only one functional type of cone in the retina (30).…”
Section: Classic Columnsmentioning
confidence: 99%
“…A V1 irányokra (tájolás) és szí-nekre reagáló lokális kis neuroncsoportjai a mitochondrialis citokróm-oxidáz-csoportoknak felelnek meg 47 . Ha a V1 neuronok kis csoportjait -durva hasonlattal -mint a tévémonitor "pixeljeit" (színegysé-gei) képzeljük el (4. ábra), akkor a vizuális percepció során aktiválódott sok millió retinotopikus neuron összehangolt elektromos tüzelése során ezen neuronokban szinkronizált biofotonok keletkezhetnek, amelyek a külsô, retinalis fotonokkal érzékelt vizuális világot a jóval gyengébb intenzitású belsô biofotonokkal újraalkothatják (rereprezentálják), így egy belsô képi reprezentáció, más néven belsô biofizikai virtuális vizuális realitás keletkezik.…”
Section: Hubel éS Wieselunclassified